Estructura de tallas, madurez gonádica y alimentación del pez Diapterus rhombeus (Gerreidae) en el sistema fluvio-deltaico Pom-Atasta, Campeche, México - Aguirre León, Arturo (2006)
Size structure, gonadic development and diet of the fish Diapterus rhombeus (Gerreidae) in the Pom-Atasta fluvial-deltaic system, Campeche, Mexico. The fish Diapterus rhombeus was studied during an annual cycle from 1992 to 1993 in the fluvial-deltaic Pom-Atasta system associated with Terminos Lagoon, Campeche, Mexico. It is a dominant species in the system, based on its numeric abundance, weight, high frequency and wide distribution. A total of 745 individuals were obtained, with a weigth of 2 890.2 g and length ranging from 3.0 to 16.7 cm. The annual variation of the allometric coefficient b was from 2.71 to 3.345. Thecondition factor varied from 0.711 to 0.934. The statistical analysis shows significant differences (p< 0.05) between the seasons of the year and the habitats of the system for the weight, the longitude and the condition factor K, which reflects the space-temporal utilization of the system for the species. The population present at Pom-Atasta, consists mainly by juvenile and few preadults individuals in gonadal stages I, II, and III, and more females than males were recorded. This species utilizes the system as a nursery area, growth and feeding area. It has a varied trophic spectrum, and consumes at least eight different groups. Its principal food items are undetermined organic matter, foraminifers, ostracods and tanaidaceans. It is a first order consumer. The Pom-Atastasystem is located in a zone of intense fishing and oil activity, so it is important to advance in the knowledge of its fishing resources.